Mitigation of what and by what? Adaptation by whom and for whom? Dilemmas in delivering for the poor and the vulnerable in international climate policy - Leisa Perch (International Policy Centre for Inclusive Growth (IPC-IG), 2011)
[Introduction] Despite notable advances in the “climate change-development” discourse and the rapid evolution of the climate-finance architecture, many of the fundamentally politicised issues that shape the existing dilemma on how to confront global climate change have been avoided or delayed. A largely market-driven response has not advanced an accountability-driven, long-term agenda, and competing interests continue to shape the discourse on adaptation and mitigation - thus influencing whose risk becomes predominant and whose impacts and losses are prioritised within and between states. This is not defined only by actions in themselves, but also by the structural reality within which policy is being shaped. In the current structure, those with the capacity to develop new technologies will have a customer base formed by those who are likely to be most vulnerable to climate change. Moreover, the extent to which we change (or can change) current patterns of consumption and production will be a reflection of the technologies available to make that change, the willingness to do so, and the level to which both adaptation and mitigation finance and projects prioritise and advance social-equity approaches, including norms for ensuring access to technology. The “energy poor” and the disenfranchised do not automatically benefit from large-scale technology-transfer projects, and some interventions help country efforts while having little impact at the community level. This raises a number of fundamental policy concerns, including the achievement of a reasonable balance within both the intent and implementation of policy, and between the imperatives of managing the climate crisis and securing development progress. Fundamentally, in the context of climate change, can we avoid what the International Union for Conservation of Nature (IUCN, 2006: 4) has referred to as often being “development as usual, with a brief embarrassed genuflection towards [in other words, paying lip-service to] the desirability of sustainability”? Using an analytical framework that combines theories of politics, “public goods”, collective action, political economy and international relations, this paper assesses current efforts and the evolving discourse on equity, with a view to reaching a better understanding of what it would take to achieve some balance between averting the worst of climate change and manage its impacts while safeguarding and enabling further progress on development. By focusing on a reasonable equity of outcomes (quality) rather than the sum of actions (quantity), the paper finds that the language used in the discourse reinforces its innately political framing, as well as prevailing governance arrangements. They in turn have led to an application of “development” that has limited the inclusion of some dimensions, namely the social, relative to others, in some cases resulting in limited direct benefits for the poor and vulnerable, missed opportunities, and a number of social risks that could undermine other development efforts. The “reinforcing role” of global policy frameworks in creating the necessary enabling environment for collective, multinational action is also given specific attention.
Keywords: 330